2002
DOI: 10.1063/1.1506384
|View full text |Cite
|
Sign up to set email alerts
|

Ion-to-CH3 flux ratio in diamond chemical-vapor deposition

Abstract: Articles you may be interested inEffect of high-voltage sheath electric field and ion-enhanced etching on growth of carbon nanofibers in highdensity plasma chemical-vapor deposition J. Appl. Phys. 98, 044313 (2005); 10.1063/1.1993776 Theoretical analysis of the diffusive ion in biased plasma enhanced diamond chemical vapor deposition Audio-frequency glow discharge for plasma chemical vapor deposition from organic compounds of the carbon family J.Methyl radicals (CH 3 ) and positive ionic species in a low-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Although in many cases carbonaceous radicals are deemed the main film precursors, ion bombardment can help decisively to film growth through the creation of dangling bonds and other reactive sites. [12][13][14] Depending on the circumstances, ions can also contribute directly to film growth. 15,16 Both positive and negative carbonated ions are assumed to play a significant role in hydrocarbon nanoparticle nucleation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in many cases carbonaceous radicals are deemed the main film precursors, ion bombardment can help decisively to film growth through the creation of dangling bonds and other reactive sites. [12][13][14] Depending on the circumstances, ions can also contribute directly to film growth. 15,16 Both positive and negative carbonated ions are assumed to play a significant role in hydrocarbon nanoparticle nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Ion−molecule reactions of H x + species and hydrocarbons are also important in other media of technological interest like those used in plasma-enhanced chemical vapor deposition (PECVD) of diamond-like and amorphous hydrogenated carbon (a-C:H) films. In these cold plasmas, hydrogenic ions contribute to formation of C x H y + species, which can play an important role in film formation. Although in many cases carbonaceous radicals are deemed the main film precursors, ion bombardment can help decisively to film growth through creation of dangling bonds and other reactive sites. Depending on the circumstances, ions can also contribute directly to film growth. , Both positive and negative carbonated ions are assumed to play a significant role in hydrocarbon nanoparticle nucleation …”
Section: Introductionmentioning
confidence: 99%
“…A common belief is that the methyl radical is the most important species for DLNC deposition, [65][66][67] this is the view put forward by Shiratani et al 67 who found that CH 3 contributed a maximum of 60% to film growth and Teii et al 68 who noted that CH 3 represented the major adspecies in diamond CVD. It has also been stated that the methyl radical is the most important species in promoting diamond-like (or sp 3 ) bonds in deposited films, 69,70 this is despite its sp 2 hybridization.…”
Section: Discussionmentioning
confidence: 92%
“…The inductively coupled plasmas are typically operated at pressures lower than 100 mTorr in the typical electron density range of 10 16 -10 18 m À3 . Such inductive plasmas have widely been used to deposit many different types of materials from inorganic films such as SiO 2 to organic polymeric films, and hard coatings such as diamond-like carbon (DLC) films, [6][7][8][9] aside from the manufacturing process in the semiconductor industries. In the plasmas, the high densities and spatially homogeneous profiles of reactive species, such as atoms, free radicals, and ions, can be achieved and the ion bombarding energy at the surface can be independently controlled.…”
Section: Introductionmentioning
confidence: 99%
“…In PECVD, the plasmas containing hydrocarbon gases, such as CH 4 and C 2 H 2 , are used to dissociate the hydrocarbon precursor gas to provide the reactive carbon species and energetic ions necessary for film growth. For example, nanocrystalline diamond has been successfully synthesized in low-pressure inductive plasmas, 9,10) showing the effect of ion bombardment on diamond growth. In inductive plasmas containing methane, the electron energy distribution function (EEDF), 8) which is essential to determine the gas-phase reaction rates, has been investigated, together with the properties of the deposited DLC films.…”
Section: Introductionmentioning
confidence: 99%